Technologies and Eco-Innovation Towards Sustainability I 2019
DOI: 10.1007/978-981-13-1181-9_19
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Sustainable Development and Design-Thinking-Based Product Design

Abstract: The aim of this research was to integrate sustainable development and design-thinking-based product design in order that the product design then contributes to society's transition to a sustainable future. This is an important pursuit since product lifecycles are a major cause of society's current sustainability challenges. To address this, many authors argue for integrating sustainable development into existing design processes rather than developing stand-alone tools and methods. Through action research with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…In any case, it could be observed that ensuring a common sustainable direction happens in the seed stage, even before cultivating the needed Dynamic Design Thinking capabilities; see Figure 5. This corresponds with the recommendations from research that sustainable development must be integrated into the entire business process "rather than merely adding 'sustainability' as an additional need" [29]. that ensuring a common sustainable direction happens in the seed stage, even before cultivating the needed Dynamic Design Thinking capabilities; see Figure 5.…”
Section: Discussion: How E-ventures' Organizational Dna Can Drive Bus...supporting
confidence: 65%
See 1 more Smart Citation
“…In any case, it could be observed that ensuring a common sustainable direction happens in the seed stage, even before cultivating the needed Dynamic Design Thinking capabilities; see Figure 5. This corresponds with the recommendations from research that sustainable development must be integrated into the entire business process "rather than merely adding 'sustainability' as an additional need" [29]. that ensuring a common sustainable direction happens in the seed stage, even before cultivating the needed Dynamic Design Thinking capabilities; see Figure 5.…”
Section: Discussion: How E-ventures' Organizational Dna Can Drive Bus...supporting
confidence: 65%
“…This notion can also be reflected for the innovation of sustainable solutions. While researchers recognize the potential of Design Thinking to innovate sustainable solutions, they note that Design Thinking only leads to sustainable product and service innovations within a sustainable framework [29,30]. With this regard, the idea of ecodesign, "a systematic approach, which considers environmental aspects in design and development with the aim to reduce adverse environmental impacts throughout the life cycle of a product" [31] is gaining importance as a concept that, in combination with Design Thinking, leads to sustainable innovation of solutions.…”
Section: Design Thinking For Product Development and Business Transfo...mentioning
confidence: 99%
“…Similarly, it is not a new idea that engineering education has a key role to play in equipping engineers with the design skills that they need to contribute to national competitiveness [3]. Owing to the importance of sustainable development in society and business [4,5], it is also clear that quality engineering education in product development has a key role to play. In addition to fundamental knowledge in maths, science, and engineering, experience of the engineering design process and the experience of realistic engineering design problems is an important aspect of engineering education.…”
Section: Introductionmentioning
confidence: 99%